2013
DOI: 10.2351/1.4824146
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser post-processing of metal parts produced by laser additive manufacturing

Abstract: High-repetition rate femtosecond laser radiation was utilized to improve surface quality of metal parts manufactured by laser additive techniques. This novel approach can be used to postprocess parts made of heat-sensitive materials, and to attain the designed net shape with micrometer precision. SummaryLaser Additive Manufacturing (LAM) is a cutting-edge manufacturing approach that is based on consecutive application of material layers and the transfer of geometrical information from the digital design data t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Selective laser melting (SLM), as a newly developed direct digital manufacturing technology, has been treated as one of the most effective powder-based additive manufacturing (AM) methods for metal parts. [10][11][12][13][14][15][16][17] During SLM process, the 3D parts are built by selectively fusing and consolidation of the thin layers of powder using the high-energy laser beam in a layer-by-layer manner according to the computeraided design (CAD) models of the parts. Because of the unique processing mechanisms of SLM, e.g., a full melting of powder materials followed by a rapid solidification at a rate up to10 6 -10 8 K/s, 18 the molten materials tend to experience a particular nonequilibrium metallurgical process during SLM processing, thereby providing a capacity to produce unique aluminum-based nanocomposite parts.…”
Section: Journal Of Laser Applications Laser Additive Manufacturing Fmentioning
confidence: 99%
“…Selective laser melting (SLM), as a newly developed direct digital manufacturing technology, has been treated as one of the most effective powder-based additive manufacturing (AM) methods for metal parts. [10][11][12][13][14][15][16][17] During SLM process, the 3D parts are built by selectively fusing and consolidation of the thin layers of powder using the high-energy laser beam in a layer-by-layer manner according to the computeraided design (CAD) models of the parts. Because of the unique processing mechanisms of SLM, e.g., a full melting of powder materials followed by a rapid solidification at a rate up to10 6 -10 8 K/s, 18 the molten materials tend to experience a particular nonequilibrium metallurgical process during SLM processing, thereby providing a capacity to produce unique aluminum-based nanocomposite parts.…”
Section: Journal Of Laser Applications Laser Additive Manufacturing Fmentioning
confidence: 99%
“…A.Y Vorobyev (2007) performed surface treatment of Ti utilising an fs laser, and they were able to produce a large variety of nanostructures on the surface of Ti material with sizes less than 20 nm [196]. also reported the utilisation of an fs laser to improve the surface quality of additive manufactured of Ti-and Ni-based alloy parts [49]. Jiao et al (2018) observed that fs laser processing on Ti6Al4V material produced nanostructures that paved the way for AM part self-cleaning and hydrophobic properties [199].…”
Section: Femtosecond Laser Processing Of Titanium and Titanium Alloysmentioning
confidence: 99%
“…As fs laser sources are capable of producing precise features at the micro and nano levels in a highly localised and controlled manner, applications at the nanomanufacturing processes [30], and micro fabrications (e.g., fabrication of micro-needles for medical applications [46]) are among the most commonly explored in the literature [47,48]. In addition, various works have explored the potential use of fs lasers for post-processing of 3D printed metallic components (i.e., utilising the associated heat to alter the microstructure) [49,50]. Further, fs laser sources were utilised to modify the flexural strength and surface morphology of materials such as translucent monolithic zirconia (for dental restoration) [51].…”
Section: Introductionmentioning
confidence: 99%
“…To improve surface finish of metal powder bed processes, some finishing operations are needed such as traditional machining [5,6], shot-peening [7,8,9], tribofinishing / vibratory finishing [10], laser polishing [11,12,13,14,15,16,17,18,19,20,21,22], chemical polishing and electrolytic polishing [5]. In this study, the focus is set on chemical polishing.…”
Section: Introductionmentioning
confidence: 99%